necrotizing fasciitis aprospective study of 18 cases at al yarmouk teaching hospital - Al kizwini, ghassan A.; Al badri, jasim A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Necrotizing fascitis is a progressive, rapidly spreading inflammatory infection located in the deep fascia, with secondary neerosis of the subcutaneous tissues polymicrobial infection is the most common finding in necrotizing fascitis rather than a single caustive organism.